2022
DOI: 10.1099/acmi.0.000483.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Diagnostic Performance of urine dipstick test for Detection of urinary tract infections in patients treated in Kenyan hospitals.

Abstract: Introduction Culture is the gold-standard diagnosis for Urinary Tract Infections (UTIs). However, most hospitals in poor-resource countries lack adequately equipped laboratories and relevant expertise to perform culture and therefore heavily rely on dipstick tests as an alternative diagnostic method for UTIs. Research gap In many Kenyan hospitals, routine evaluations are rarely done to assess the reliability of popular screening tests such as the dipstick test. As such, there is a high risk of misdiagnosis e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…The test has poor positive predictive value and minimal agreement with culture (kappa, 0.23). The LE sensitivity of 62.2% reported by Maina et al [11], 60% by Dadzie et al [17] and 48% by Anith et al [9] were all higher than the nitrite test, which mirrors that of the present study. Despite being more sensitive than nitrites, the LE test is not specific for UTI and may be associated with other inflammatory disorders affecting the urinary tract such as vaginitis, chlamydial urethritis or other infections than can elicit an immune response and production of white blood cells [32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The test has poor positive predictive value and minimal agreement with culture (kappa, 0.23). The LE sensitivity of 62.2% reported by Maina et al [11], 60% by Dadzie et al [17] and 48% by Anith et al [9] were all higher than the nitrite test, which mirrors that of the present study. Despite being more sensitive than nitrites, the LE test is not specific for UTI and may be associated with other inflammatory disorders affecting the urinary tract such as vaginitis, chlamydial urethritis or other infections than can elicit an immune response and production of white blood cells [32].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, consideration of urine dipstick positivity as 'either NIT+ or LE+' reported a positivity rate of 34%. This compares to prior dipstick positivity reports of 54% by Maina et al in a similar study in Kenya [11], 73% by Katunzi et al in Tanzania [20] and 34% by Dadzie et al in Ghana [17].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Despite these metrics advocating for their use in preliminary screening, the test's limitations necessitate confirmation by culture for a definitive diagnosis. This study highlights the unreliability of dipsticks for accurate UTI detection in children with SCD, noting discrepancies in prevalence rates compared to culture methods and the risk of false results [ 24 , 25 ]. Consequently, clinicians should not rely solely on the dipstick test for UTI screening, emphasizing the need for corroborative diagnostics.…”
Section: Discussionmentioning
confidence: 99%